TED072 : Basic principles in education / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2018)
The course introduces students with basic principles in education as well as various aspects of the teaching profession, including effectivenesss in teaching, classroom ecology, motivation in learning, etiquette, practice and professional development. The course exposes students to the school environment through dialogue with practicing teachers and through visits to pre-elementary and secondary schools. This course also provides students with an overview of the Malaysian education system and the National Philosophy of Education.